The Pine Branch, January 1919 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the South Georgia State Normal College., 1919)
The Pine Branch. Periodical magazine. Created and published by the Students of South Georgia State Normal College, Valdosta, Georgia. Includes: editorials, photographs, poems, short stories, and other writings.
New Year's Eve in Spooky Town- Poem, President's Letter Life Sketches, Lelya Freison - Ruth Browne, A Psalm of Life - Poem, Ghost Land - Frances Bitzer, In France Today - Poem, Speakin' of Rain - Poem, Editorials, Alumnae, Humorous, It Pays to Advertise - Acrostic,
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; South Georgia State Normal College; Valdosta; Schools--Georgia; Education